Cycle Time Analysis Of AS/RS (Automated Storage & Retrieval System) Using SCADA - Fahreza, Dadang Suriana; Risfendra, Risfendra (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
AS/RS is not just a replacement for conventional warehouses, but has become a key element in modern manufacturing systems. However, in its use there are still problems and shortcomings, including the unavailability of a system that can control, supervise, and acquire data from AS/RS and the cycle time when AS/RS performs data storage and retrieval tasks is still below industry standards. To overcome this, a system that is generally called SCADA (Supervisory, Control, and Data Acquisition) is needed. This research uses Arduino Mega 2560 as an AS/RS controller, while the VTSCADA application is used to build a SCADA system on AS/RS. This research uses two approaches. First, calculating the AS/RS cycle time when performing storage and retrieval tasks. Second, comparing the cycle time of the storage system and the retrieval system. The first test results show that the fastest cycle time in the storage system occurs at storage rack point 1 with a time of 3.17 seconds, while the fastest cycle time in the retrieval system occurs at retrieval point 1 with a time of 12.74 seconds. The second test resulted in a difference in cycle time between the storage and retrieval systems, namely 0.42 seconds at storage point 1, 0.38 seconds at storage point 2, 0.51 seconds at storage point 3, 0.31 seconds at storage point 4, and 0.43 seconds at storage point 5. It can be concluded that the application of SCADA to AS/RS is able to increase the cycle time of AS/RS.